FAKTOR PENENTU KINERJA PEGAWAI PADA DINAS PERDAGANGAN KABUPATEN MAMUJU - Mariana, Lina (Jurnal Ilmu Manajemen Profitability, 2020)
The study aims to determine and analyze the effect of employee competence on employee performance in the Mamuju district trade service, analyze the influence of work culture on the performance of the Mamuju district trade service employee. The research approach is quantitative descriptive with a sample of 40 respondents, data processing using SPSS 22 using multiple linear regression analysis. The results showed that; The determining factor for employee performance in the Mamuju Regency trade office is organizational culture.